Proceedings of SPE Annual Technical Conference and Exhibition 2000
DOI: 10.2523/63050-ms
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Drilling Fluid Properties and Flow Rates For Effective Hole Cleaning in High-Angle and Horizontal Wells

Abstract: fax 01-972-952-9435. AbstractThis paper presents a method to determine optimum drilling fluid properties and flow rates to minimize cuttings bed height and circulation time in high angle and horizontal wells. The method uses empirical models relating the cuttings bed height and the bed erosion time to drilling fluid properties and flow rates.Bed erosion tests have been conducted using a cuttings transport facility available at the University of Tulsa. Cuttings bed height as a function of time has been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…This may prevent bed formation and improve hole cleaning efficiency [20]. Thus hole cleaning efficiency relies on non-controllable annular eccentricities to remove cuttings or prevent bed formation [3].…”
Section: Operational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may prevent bed formation and improve hole cleaning efficiency [20]. Thus hole cleaning efficiency relies on non-controllable annular eccentricities to remove cuttings or prevent bed formation [3].…”
Section: Operational Factorsmentioning
confidence: 99%
“…While drilling a vertical well, the hole cleaning process is easier and does not represent complex challenges due to the small area for cuttings accumulation and the fact that the drilling fluid flows in opposite direction to gravity. Hence, cuttings transportation can be controlled by high viscosity and ensuring good gel formation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Han et al, (2010) carried out an experimental study using CFD on cuttings transport in vertical as well as greatly deviated slim annular hole and the study result showed that pressure drop in a solid-liquid mixture flow increases with mixture flow rate, annular inclination and DP rotation speed [11]. According to Adari, et al, (2000) controlling cuttings transport practically is much dependent on the field conditions encountered. To ensure effective and efficient hole cleaning, transport of cuttings in the annulus usually are not affected by one parameter but a whole lot of parameters [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to Adari, et al, (2000) controlling cuttings transport practically is much dependent on the field conditions encountered. To ensure effective and efficient hole cleaning, transport of cuttings in the annulus usually are not affected by one parameter but a whole lot of parameters [15]. Despite several studies in the literature on ECD, no significant attention was paid on the influence of drill cuttings on ECD.…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, the drilling tools may be broken, causing serious engineering accidents, such as sticking [8][9][10]. Many controllable and uncontrollable factors are involved in the hole-cleaning process (i.e., the cuttings-carrying process), such as the flow velocity in the borehole annulus, the displacement of the mud pump, the viscosity of the drilling fluid, the rotational speed of the drill pipe, and the diameter of the bit waterway [11,12].…”
Section: Introductionmentioning
confidence: 99%